Entrepreneurs Are Not Utilizing Online Equity Crowdfunding - Stanberry, Kurt (Journal of Applied Business and Economics, 2023)
This is a policy paper discussing online equity crowdfunding for small business entrepreneurs, and analyzes the low success rate of this relatively new financing technique. Created by the JOBS Act, the online equity crowdfunding program was designed to improve access to capital markets for small businesses, and first became available in 2016. The five year success rate is rather limited. Data collected by the SEC on online equity crowdfunding for small business owners shows disappointing rates of utilization. In essence, the concept has not delivered on the promise of increasing capital access for small business owners.